Impaired vibrotactile sense in children and adolescents with type 1 diabetes – Signs of peripheral neuropathy - Ising, Erik; Dahlin, Lars B.; Elding Larsson, Helena (PloS one, 2018)
To investigate whether multi-frequency vibrometry can identify individuals with elevated vibration perception thresholds (VPTs), reflecting impaired vibrotactile sense, among children and adolescents with type 1 diabetes. In 72 pediatric patients with type 1 diabetes, VPTs were evaluated for seven frequencies on two sites of the hand, and five frequencies on two sites of the foot. Z-scores, based on previously collected reference data, were calculated. Perception to light touch was investigated using monofilaments. Subjects' characteristics were analyzed in comparison to normal and impaired vibrotactile sense. Subjects' median age, disease duration and age at disease onset were 12.8, 5.3 and 6.9 years, respectively. A total of 13 out of 72 (18%) subjects had impaired vibrotactile sense on at least one foot site. Impaired vibrotactile sense was more common among subjects treated with multiple daily insulin injections (MDI) compared to subjects treated with continuous subcutaneous insulin infusion (CSII) (p = 0.013). Age at disease onset was higher among subjects with impaired vibrotactile sense (p = 0.046). No significant correlations were found with gender, HbA1c or duration of diabetes. Impaired vibrotactile sense, mirroring diabetic peripheral neuropathy, was found in 1/5 of the children and adolescents in the study, and was more common in patients treated with MDI than in subjects treated with CSII.